2021
DOI: 10.5483/bmbrep.2021.54.4.183
|View full text |Cite
|
Sign up to set email alerts
|

CD1d deficiency limits tolerogenic properties of peritoneal macrophages

Abstract: Invariant natural killer T (iNKT) cells are involved in various autoimmune diseases. Although iNKT cells are arthritogenic, transforming growth factor beta (TGFβ)-treated tolerogenic peritoneal macrophages (Tol-pMφ) from wild-type (WT) mice are more tolerogenic than those from CD1d knock-out iNKT cell-deficient mice in a collagen-induced arthritis (CIA) model. The underlying mechanism by which pMφ can act as tolerogenic antigen presenting cells (APCs) is currently unclear. To determine cellular mechanisms unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…They are commonly found at the cartilage–pannus junction and in inflammatory synovial membranes. The extensive proinflammatory, destructive, and remodeling abilities of macrophages play an important role in both acute and chronic phases of RA 71 . TNF-α and interleukin-1 are two pro-inflammatory cytokines secreted by M1 macrophages, and several experimental and clinical studies have demonstrated their importance in the pathophysiology of RA 72 , 73 .…”
Section: Discussionmentioning
confidence: 99%
“…They are commonly found at the cartilage–pannus junction and in inflammatory synovial membranes. The extensive proinflammatory, destructive, and remodeling abilities of macrophages play an important role in both acute and chronic phases of RA 71 . TNF-α and interleukin-1 are two pro-inflammatory cytokines secreted by M1 macrophages, and several experimental and clinical studies have demonstrated their importance in the pathophysiology of RA 72 , 73 .…”
Section: Discussionmentioning
confidence: 99%
“…Upon LPS stimulation, macrophages from CD1d +/− mice exhibited a more anti-inflammatory profile, characterized by increased secretion of IL-10 and decreased secretion of TNF-α and IL-6. This further reflected in disease amelioration following adoptive transfer of CD1d +/− peritoneal macrophages into CD1d KO mice with CIA [115].…”
Section: The Inkt Cell-macrophage Axis In Autoimmunitymentioning
confidence: 94%
“…By using a murine model of collagen-induced arthritis (CIA), Miellot-Gafsou et al observed that hepatic iNKT cells underwent activation during the early phase of the disease, with CD1d blocking in early but not in late disease stages decreasing CD40 expression on macrophages and DCs and ameliorating disease manifestations [114]. Contrarily, a recent report has underpinned that iNKT cells contribute to key immunosuppressive roles of peritoneal macrophages in CIA mice to promote immunological tolerance [115]. Although peritoneal macrophages from CD1d +/− and CD1d − mice did not register major differences in expression of distinct M1 and M2 cell surface markers, their cytokine profiles varied.…”
Section: The Inkt Cell-macrophage Axis In Autoimmunitymentioning
confidence: 99%
“…Besides, macrophages are professional antigen-presenting cells (APCs). They can engulf pathogens or particles through phagocytosis and break down these substances within lysosomes, thus presenting them to helper T cells (CD4 + T cells) [ 38 ]. This interaction is essential for activating and coordinating adaptive immune responses.…”
Section: Normal and Diabetic Wound Healingmentioning
confidence: 99%